Corrigendum to “Multifunctional soft machines based on stimuli-responsive hydrogels: from freestanding hydrogels to smart integrated systems” [Mater Today Adv 8 (2020) 100088](S2590049820300357)(10.1016/j.mtadv.2020.100088) - Ding, M. (Elsevier Ltd, 2022)
10.1016/j.mtadv.2020.100130